Cardiovascular adverse reactions associated with escitalopram in patients with underlying cardiovascular diseases: a systematic review and meta-analysis - Shizukawa, Kenichi; Narita, Hisashi; Imai, Hissei; Akiyama, Hisashi; Ishikawa, Shuhei; Sawagashira, Ryo; Isoyama, Tomoyuki; Nohara, Mariko; Kawamura, Michiyo; Kono, Yukari; Saito, Takuya; Kusumi, Ichiro (Frontiers in Psychiatry, 2023)
Background: Despite the anticipated efficacy of escitalopram in treating depression and anxiety in individuals with preexisting cardiovascular conditions, persistent concerns regarding its adverse effects have emerged. In this systematic review, we aimed to evaluate the cardiovascular safety profile of escitalopram compared with that of placebo in patients with underlying cardiovascular disease.We used a predefined search strategy in PubMed, Cochrane Central Register of Controlled Trials, Embase, International Clinical Trials Registry Platform, and ClinicalTrials.gov to identify studies evaluating adverse cardiovascular reactions to escitalopram in patients with underlying cardiovascular disease. Randomized controlled trials (RCTs) that provided results on cardiovascular safety outcomes were included. Two independent reviewers screened the abstracts and full texts of the individual studies. The risk of bias was assessed using version 2 of the Cochrane risk-of-bias tool for randomized trials. The certainty of evidence was assessed using the Grading of Recommendations, Assessment, Development, and Evaluation approach.Results: The primary outcomes were the frequency of major adverse cardiovascular events (MACE), QTc prolongation, and discontinuation of study medication. We identified 5 RCTs with 773 participants who met the inclusion criteria. Escitalopram was not associated with significantly This is a provisional file, not the final typeset article increased risk of MACE (risk ratio [RR] = 1.85; 95% confidence interval [CI] 0.80 to 4.26; I 2 0%; 5 RCTs; n = 773, moderate certainty of evidence), discontinuation of study medication (RR = 1.03; 95% CI 0.84 to 1.26; I 2 0%; 5 RCTs; n = 773, low certainty of evidence), and QTc prolongation (RR = 1.20; 95% CI 0.76 to 1.90; I 2 0%; 4 RCTs; n = 646, low certainty of evidence).Escitalopram does not significantly increase the risk of cardiovascular adverse reactions compared with placebo in patients with underlying cardiovascular disease. However, the presence of wide CIs and the limited number of included studies highlight the need for further studies with larger sample sizes to enhance the precision and reliability of these findings.